MySAP ERP for dummies - Vogel, Andreas, 1965- (--For dummies., 2005)
SAP is the world's leading provider of ERP software and services, with worldwide revenue in 2004 of 9.7 billion and a 57 percent market share among major business application providers; it is one of the world's largest software companies overallERP is a flexible, open technology platform that helps businesses run more efficiently (and profitably) by providing integrated management of key operations and supply chainsWritten for IT professionals who find it hard to get through SAP's complex documentation, our book demonstrates how ERP can cut costs, provides a clear overview of.